Comparison of the Efficacy of Absorbable Versus Non-Absorbable Sutures after Lichtenstein Mesh Hernioplasty Regarding Post Operative Pain - Farhan Javaid, M. Usama Shabbir, Mohammad Akmal Shafiq, Muhammad Asadullah Khawaja (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Comparison of the efficacy of absorbable versus non-absorbable sutures after Lichtenstein mesh hernioplasty. Methodology: We planned this Randomized Control Trial consisting of 200 cases, from Surgical outdoor booked for hernioplasty. All patients were examined in a comfortable environment. All the information was kept confidential. The patients were not aware of the randomization arm and selected via lottery method. All patients underwent Lichtenstein mesh hernioplasty under local anesthesia. Before surgery, a course of prophylactic antibiotics consisting of 1 g of IV cefazolin was administered to each patient. All procedures were done by skilled post graduate general surgical residents under consultant supervision. Predictable bias and confounding factors were controlled by restriction (inclusion and exclusion criteria) and randomization. Rest was addressed during final analysis through stratification. GROUP A patients undergo mesh fixation using Prolene 1. (non-absorbable) GROUP B patients undergo mesh fixation using Vicryl 0. (absorbable). For all treatments, a conventional tension-free uniformed surgical method was adopted. Patients were evaluated at 3 months followup to record the efficacy. Results: Mean age was calculated as 44.7+9.45, mean pain score on VAS was calculated as 2.04+0.72 in Group-A and 1.54+0.76 in Group-B,p-value=0.018. Comparison of efficacy of absorbable versus non-absorbable sutures after Lichtenstein mesh Hernioplasty shows that 83(n=83%) in Group-A and 94(n=94) in Group-B had efficacy while, p value 0.014 showing a significant difference. Conclusion: Our findings indicate that, following Lichtenstein mesh hernioplasty, absorbable suture is more effective than non-absorbable suture regarding post operative pain. Keywords: Inguinal hernia, hernioplasty, absorbable versus non-absorbable sutures, efficacy